STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) DALAM MENINGKATKAN PELAYANAN JAMAAH LANSIA PADA PENYELENGGARAAN IBADAH HAJI KHUSUS (PIHK) - Djadjang Sudradjat (Jurnal Ekonomi dan Bisnis, 2026)
The increasing number of elderly Hajj pilgrims in Indonesia requires more professional and humane services in the implementation of special Hajj services. This study aims to analyze human resource (HR) development strategies in improving services for elderly pilgrims at the Special Hajj Organizers (PIHK). The research method used is library research with a descriptive qualitative approach. Data were obtained from books, scientific journals, government regulations, and previous studies relevant to HR development and elderly pilgrim services. The results of the study indicate that HR development strategies are carried out through elderly-friendly service training, improvement of officers’ technical and emotional competencies, performance evaluation, strengthening interpersonal communication, and utilization of information technology in pilgrim services. Sustainable HR development is able to improve service quality, comfort, safety, and satisfaction of elderly pilgrims during the Hajj pilgrimage. Therefore, PIHK needs to optimize HR development so that services for elderly pilgrims can run effectively, professionally, and in accordance with pilgrims’ needs.